Hydrocarbon generation potential of a Lower Permian sedimentary succession (Mount Agony Formation): Southern Sydney Basin, New South Wales, Southeast Australia - Maravelis, A.; Chamilaki, E.; Pasadakis, N.; Zelilidis, A.; Collins, Bill (Elsevier BV, 2017)
This research presents a comprehensive approach on the hydrocarbon generation potential applied for the first time on the Lower Permian Mount Agony Formation that is exposed in the southern Sydney Basin, southeast Australia. Thirty mudstone samples were collected and analyzed using different organic geochemical methods such as, Rock-Eval VI-TOC, bitumens extraction, and GC–MS analysis. Attributes such as, quantity, quality and maturity of the organic matter were utilized to estimate the regional source rock potential. The obtained data indicate that the examined samples have poor to good, dominantly gas-prone source-rock potential, and contain a mixed in origin organic matter. The slight predominance of terrestrial organic material is indicated by the low odd to even predominance values, slight predominance of higher n-alkanes over short-chain n-alkanes, OEP25–33, CPI25–33, ACL25–33, and TAR values. Some availability of marine organic material is evidenced by the predominance of intermediate chain n-alkanes and the low n-C19/n-C31 and n-C24 +/n-C24– ratios. The analyzed sediments are thermally mature, as suggested by the Tmax, PI, OEP 25–33 and CPI25–33 values, the Pr/n-C17, Ph/n-C18, C30-moretane/C30-hopane, Ts/(Ts + Tm) and C32S/(S + R) ratios, as well as by the C30-moretane/C30-hopane versus Tm/Ts plot. A mudstone-rich, siliciclastic source rock is implied by the C29/C30 hopane ratios and by the Ts/(Ts + Tm) versus 23tricyclic/hopane cross-plot. This research offers original organic geochemical data of a sedimentary succession that was not so far regarded as source rock. This study adds to the knowledge available for the types of potential reserves in the Southern Sydney Basin, which are mostly focused on coal and coal-seam gas resources.